2020
DOI: 10.1063/1.5142043
|View full text |Cite
|
Sign up to set email alerts
|

An SEM compatible plasma cell for in situ studies of hydrogen-material interaction

Abstract: An in-situ hydrogen (H) plasma charging and in-situ observation method was developed to continuously charge materials while tensile testing them inside a scanning electron microscope (SEM). The present work will introduce and validate the setup and showcase an application allowing high-resolution observation of H-material interactions in a Ni-based alloy, the alloy 718. The effect of charging time and pre-straining was investigated.Fracture surface observation showed the expected ductile microvoid coalescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The Monte-Carlo program STrim.SP 6.0D gave a r mean =1.15 nm and that 41% of the particles are implanted. From Langmuir Probe measurements [ 40 ], the ion flux was calculated to be 10 20 m −2 s −1 . Table 3 shows the recombination coefficients that were calculated according to refs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Monte-Carlo program STrim.SP 6.0D gave a r mean =1.15 nm and that 41% of the particles are implanted. From Langmuir Probe measurements [ 40 ], the ion flux was calculated to be 10 20 m −2 s −1 . Table 3 shows the recombination coefficients that were calculated according to refs.…”
Section: Resultsmentioning
confidence: 99%
“… where C max is the maximum lattice H concentration, η the ion flux, and k f the recombination coefficient. The ion flux was calculated from Langmuir Probe measurements and it is described in detail in [ 40 ]. A Monte-Carlo program, SDTrim.SP 6.0 [ 44 ] was used for estimating the implanted fraction/particle reflection yield and the mean implantation range.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter was also reported to affect the activity of dislocations [76]. Recently, some novel setups combining in situ H charging (performed using H plasma [77] or electrochemically [78]) and SEM observation have been developed, which opens new possibilities of studying the H effect in a more comprehensive manner. For example, Depover and Wan et al [74,79] have shown that the H plasma charging provides the possibility to in situ charge ferritic or dual-phase materials without causing significant damages on the sample surface.…”
Section: Small-scale In Situ Tensile Tests In Semmentioning
confidence: 99%
“…Critical hydrogen sources are present during materials processing as well as during service [12,13]. Hydrogen can be absorbed at the surface, resulting in an inhomogenous hydrogen distribution [14][15][16][17] in the steels, which is strongly influenced by plastic deformation [18], residual stresses and edge conditions [19][20][21][22]. Hydrogen desorption at room temperature is a crucial problem during testing of hydrogen embrittlement [23], which makes determining the hydrogen embrittlement threshold for a given hydrogen content difficult.…”
Section: Introductionmentioning
confidence: 99%